Elevated expression of protein arginine methyltransferase 5 predicts the poor prognosis of breast cancer - Ying Wu; Zhe Wang; Jian Zhang; Rui Ling (Tumor Biology)
Protein arginine methyltransferase 5 is one of the type II protein arginine methyltransferase family members that can symmetrically dimethylate arginine residues on target proteins in both the cytoplasm and the nucleus. Protein arginine methyltransferase 5 was reported to be an oncoprotein that participates in tumor progression through both epigenetic silencing and organelle biogenesis. So far, it has been implicated in various cancers, but its expression pattern in breast cancer has not been elucidated thoroughly. We analyzed the protein arginine methyltransferase 5 expression patterns in several breast cancer samples and tissue arrays to better characterize its contribution to breast cancer. Primary breast tumors showed increased protein arginine methyltransferase 5 expression compared with adjacent normal tissues in both the fresh tissue samples and tissue arrays. Also, there was a tendency that metastatic lymph nodes demonstrated enhanced protein arginine methyltransferase 5 expression compared to primary sites. Moreover, we found a significant correlation between protein arginine methyltransferase 5 and Ki-67, with higher Ki-67 and protein arginine methyltransferase 5 expressions in primary breast tumors compared with normal breast tissues. Moreover, the Cancer Genome Atlas cohort analysis revealed that high protein arginine methyltransferase 5 messenger RNA expression was associated with an unfavorable prognosis in human epidermal growth factor receptor 2 (HER-2) positive and triple negative breast cancer patients. Finally, the roles and mechanisms of protein arginine methyltransferase 5 in the proliferation, cell cycle progression, and apoptosis of MDA-MB-231 cells were assessed using protein arginine methyltransferase 5 and shPRMT5 transfection. In conclusion, we proposed that protein arginine methyltransferase 5 is an independent prognostic biomarker for breast cancer, and targeting protein arginine methyltransferase 5 might be a promising strategy for breast cancer treatment.